Hydrodynamics of an FCC riser using energy minimization multiscale drag model - Shah, Milinkumar; Utikar, Ranjeet; Tade, Moses; Pareek, Vishnu (Elsevier BV, 2011)
In this study, a structured-based drag was derived using the energy minimization multiscale (EMMS) model, and used to carry out computational fluid dynamics (CFD) simulations for low and high solid flux fluid catalytic cracking (FCC) risers. The results were compared with those using the Gidaspow drag model, as well as experimental data and previous simulation results. Initially, the EMMS model was solved for two flow conditions and the correlations for the drag coefficients were derived, which were then used to simulate 2D domain of the risers. The time-averaged axial and radial profiles of voidages and pressured drop were compared with the experimental data. The comparison showed that only EMMS model was able to capture the axial heterogeneity with the dense bottom and dilute top sections. The radial profiles using both drag models showed only qualitative agreement with the experimental data. The results using the EMMS and Gidaspow drag model showed a reasonable agreement near the wall and the centre, respectively. Thus, it was concluded that the EMMS model was able to predict both axial and radial heterogeneity for both flow conditions, but only qualitatively; however, further improvements are required to achieve quantitative agreement with the experimental data.